Effect Of Different Feeding Systems On Growth Performance And Cost Economics In Mecheri Lambs. - Arulnathan , N.; Bandeswaran , C. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A study was carried out to assess the growth performance and cost economics of different feeding systems, which could be adopted by the farmers for their benefits. The average daily gain was significantly higher (P<0.01) in Gr-I (50.08 g) than Gr-II (36.84 g) and Gr-III (29.34 g). Overall body weight gain of Gr I were significantly (P<0.01) higher than Gr II and Gr III. The net profit was the highest in Gr I. In this study average daily gain and net profit was higher in lambs maintained in Gr-I (stall feeding) than Gr-II (Grazing +Concentrate feeding) and Gr-III (grazing alone). The plane of nutrition in Gr I had significantly contributed to the superior body weight gain and net profit.